Emergency Pharmacist Impact on Health Care-Associated Pneumonia Empiric Therapy. (April 2013) - DeFrates, Sean R.; Weant, Kyle A.; Seamon, Jason P.; Shirakbari, Alicia; Baker, Stephanie N.
Purpose: Health care-associated pneumonia (HCAP) is a serious infection dependent on proper treatment that often presents in the emergency department (ED) and deviation from treatment guidelines appears to be high. This study was conducted to evaluate the impact of emergency medicine pharmacists (EPhs) on adherence of empiric antibiotic therapy to guideline recommendations. Methods: A retrospective chart review of adult patients with HCAP who presented to an academic medical center ED from September 1, 2008 to June 30, 2010 was conducted. The control group included those patients with HCAP who presented to the ED outside of the EPhs' hours (23:00-13:00), and the treatment group consisted of those patients who presented during the EPhs' hours (13:00-23:00). Results: The 81 patients presenting inside the EPhs' hours were significantly more likely to receive guideline adherent empiric antibiotics than the 70 patients presenting outside the EPhs' hours (49.38% vs 25.7%, P = .005). Also, patients in the treatment group received antibiotics in a shorter amount of time (11.37 vs 15.56 hours, P = .272) and at more appropriate doses (85.2% vs 77.1%, P = .29) although these outcomes were not statistically significant. Conclusion: The presence of the EPh significantly increased the likelihood of at-risk patients receiving empiric antimicrobial therapy consistent with guideline recommendations.